2021
DOI: 10.1021/acs.iecr.1c02343
|View full text |Cite
|
Sign up to set email alerts
|

Cascade Synthesis of l-Homoserine Catalyzed by Lyophilized Whole Cells Containing Transaminase and Aldolase Activities: The Mathematical Modeling Approach

Abstract: Aldolase and transaminase coexpressed in Escherichia coli cells and lyophilized (i.e., lyophilized whole-cell biocatalyst (LWCB)) were used as biocatalysts for the one-pot cascade synthesis of L-homoserine with substrate cycling. The kinetic analysis of enzymes within lyophilized cells was performed to evaluate the behavior of the system. The best result among the performed fed-batch reactor experiments achieved was 640.8 mM (76.3 g L −1 ) of L-homoserine with a volume productivity of 2.6 g L −1 h −1 . This is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
(123 reference statements)
0
6
0
Order By: Relevance
“…Pyruvate aldolase reversibly mediates the C–C bond formation between pyruvate and aldehydes to produce 4-hydroxy-2-ketoacids that are less exploited in organic synthesis. Pyruvate aldolase is a potential biocatalyst for condensing formaldehyde and pyruvate to produce 2-keto-4-hydroxybutyrate, a valuable building block for the synthesis of l -homoserine, 3-hydroxypropionic acid, and 1,3-propanediol, which are important starting materials in the manufacture of biocompatible plastic and polytrimethylene terephthalate. , In this regard, the high production of 2-keto-4-hydroxybutyrate from cheap materials is of great interest. Recently, 2-keto-4-hydroxybutyrate as an intermediate in metabolic pathways has been produced by several enzymes, such as 2-keto-3-deoxy- l -rhamnonate aldolase from Escherichia coli ( Ec YfaU), 2-keto-4-hydroxybutyrate aldolase from E.…”
Section: Introductionmentioning
confidence: 99%
“…Pyruvate aldolase reversibly mediates the C–C bond formation between pyruvate and aldehydes to produce 4-hydroxy-2-ketoacids that are less exploited in organic synthesis. Pyruvate aldolase is a potential biocatalyst for condensing formaldehyde and pyruvate to produce 2-keto-4-hydroxybutyrate, a valuable building block for the synthesis of l -homoserine, 3-hydroxypropionic acid, and 1,3-propanediol, which are important starting materials in the manufacture of biocompatible plastic and polytrimethylene terephthalate. , In this regard, the high production of 2-keto-4-hydroxybutyrate from cheap materials is of great interest. Recently, 2-keto-4-hydroxybutyrate as an intermediate in metabolic pathways has been produced by several enzymes, such as 2-keto-3-deoxy- l -rhamnonate aldolase from Escherichia coli ( Ec YfaU), 2-keto-4-hydroxybutyrate aldolase from E.…”
Section: Introductionmentioning
confidence: 99%
“…However, the aminotransferases‐mediated amino transfer reactions between α‐amino acids and α‐keto acids were usually suffered unfavorable thermodynamic equilibrium because of the low equilibrium constant ( K eq = 1) (France et al, 2016; Zhu & Hua, 2009). Therefore, shifting reaction equilibrium to product was one of the most critical issues for the efficient transaminase reaction (Kelefiotis‐Stratidakis et al, 2019; Satyawali et al, 2019), and employing multienzyme cascade to circumvent this issue was highly required (Česnik Katulić et al, 2021; Simon et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Multi‐enzyme cascades allow, e. g., more complex synthesis routes, the use of low concentrations of co‐substrates [11] and cofactors [12] enabled by their regeneration, the modification of reaction equilibria, the removal of co‐products, [13,14] or the further reaction of (unstable) intermediates, avoiding inhibition by an accumulation of products as well as additional isolation, protection, and deprotection steps [2] . As such, amine transaminases (ATAs) have often been combined with other enzymes, such as with an aldolase for simultaneous co‐product removal and substrate recycling using the co‐product, [15] or with a pyruvate decarboxylase for co‐product removal [14,16] …”
Section: Introductionmentioning
confidence: 99%
“…To date, many studies have addressed the immobilization of catalases [37,38,39] and d ‐AAOs, [40,41,42] and also the co‐immobilization of both, [43,44] whereas immobilization of l ‐AAOs [18,45] was performed in fewer studies mainly attributed to the obstacles in producing stable l ‐AAOs in soluble form [21,46] . In addition, although transaminases were immobilized in several studies, their co‐immobilization with other enzymes was reported only rarely, [15,47] and a combination with a l ‐AAO and a catalase was not demonstrated at all.…”
Section: Introductionmentioning
confidence: 99%